Model-based Analysis of Respiratory Mechanics and Parameters in Critically Ill Mechanically Ventilated Patients - Ang, Christopher Yew Shuen; Chiew, Yeong Shiong; Wang, Xin; Nor, Mohd Basri Mat (2022 IEEE-EMBS Conference on Biomedical Engineering and Sciences (IECBES), 2022)
Mechanical ventilation (MV) parameters and other physiological parameters determined from mechanically ventilated respiratory failure patients can be used to estimate patient-centred outcomes. However, there is a lack of analysis of these ventilation parameters continuously to provide useful clinical insight into patients' disease state, progression as well as evaluation of MV treatment management. This paper presents a model-based analysis on patient-specific respiratory mechanics and MV breath parameters for a clinical observational trial. This study includes 15 patients, with 24 hours of MV data analysed per patient. A total of 385,438 breaths were analysed for this patient cohort. Model-based identification of patient-specific respiratory mechanics yielded a median [interquartile range, IQR] E rs and R rs of 28.66 cmH 2 O/L [24.81-35.92] and 8.86 cmH 2 O/L/s [6.11-12.78]. Out of 15 patients, 10 patients have less than 10% of MV parameters (V T , P Plat , PIP, driving pressure, PEEP and MP) falling into the safe ranges described by lung protective strategies and in literature. Analysis of patient arterial blood gas values (ABG) yielded a median PaCO 2 , PaO 2 and pH of 38.0 mmHg [31.7-43.0], 90.2 mmHg [73.9-119.0], and 7.38 [7.32-7.42] respectively. Respiratory mechanics, parameters and haemodynamics are patient-specific and time-varying. Model-based methods enable continuous, concurrent, and real-time monitoring of breath parameters, aiding clinicians in titrating and providing an optimal balance between various ventilator settings while preventing patient harm.Clinical Relevance-Simultaneous and real-time analysis of patient-specific respiratory mechanics and parameters in this clinical observational trial show low compliance rates with respect to lung protective strategies in mechanical ventilation treatment.